OPTIMASI LAMA WAKTU FERMENTASI LIMBAH SAYUR DENGAN CAIRAN RUMEN TERHADAP PENINGKATAN KANDUNGAN NUTRISI PAKAN IKAN NILA (OREOCHROMIS NILOTICUS) - Murni Murni; Darmawati Darmawati; Muhammad Irwandi Amri (Universitas Muhammadiyah Makassar, 2017)
The purpose of this study was to determine the length of time vegetable waste fermentation with rumen fluid effective in improving the nutritional quality of tilapia fish feed. Fermentation is carried out in rumen fluid after fermentation is complete, the fermented vegetable waste is dried and subsequently roasted proximate analysis and total sugars. In this study, there were four treatments, three days (treatment A), 4 days (treatment B), 5 days (treatment C), and 6 days (treatment D). The results obtained during the study showed that the use of rumen fluid in the fermentation process of vegetable waste was not significant (P 0.05) on the content of moisture, crude protein, fat, crude fiber, ash and extract materials without nitrogen (BETN) and the content of total sugars